FREKUENSI PENGGUNAAN BAHASA JEPANG MAHASISWA - Ribka Ribka; Nana Rahayu; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The frequency of use of Japanese is defined as the level of frequency or infrequentness of language activities or language activities of students of the Japanese Language Education Study Program in the form of listening, speaking, reading and writing activities indicated by adverbs of frequency, such as always, often, rarely, and never. The purpose of this study was to find out how high the frequency of using Japanese by students of the Japanese Language Education Study Program, Riau University. The method used in this research is descriptive with a quantitative approach. Quantitative descriptive is a type of research that is used to explain a phenomenon as it is by using numbers that describe the characteristics of the subject. The results showed that the level of frequency of using Japanese is in the category of rarely and never using Japanese. Factors causing linguistic input are less quantity, teaching and learning strategy factors applied by lecturers do not encourage students to use Japanese more, environmental factors do not stimulate the growing need for Japanese.Key Words: frequency, use of Japanese, causative factor